Uncertainties around incretin-based therapies: A literature review - Bader Al Tulaihi; Samia Alhabib (Elsevier, 2017)
Background: Diabetes mellitus is a chronic debilitating and non-communicable disease. It has several long-term outcomes that are associated with various end organ damage, mainly the heart, blood vessels, eyes, nerves, and kidneys. There are different modalities of treatment of diabetes. The recent incretin-based therapies provided an innovative class of drugs including GLP-1 receptor agonists and DPP-4 inhibitors. This review aims to summarize the available evidence of their effectiveness. Method: This is a narrative review. Several databases were searched. Search terms used were MeSH and keywords with different combinations of Boolean operators according to the database but were comparable. Studies included were: randomized controlled trials, cohort and case-controlled studies, health technology report, meta-analysis, and systematic reviews. Results were analysed and reported in a narrative style with emphasis on the effectiveness and adverse effects of various types of incretin based therapies. Results: 17 articles were retrieved as they fulfilled the inclusion criteria. They were heterogeneous in terms of interventions, participants, settings and outcomes. Studies varied in their quality and/or reporting of their findings conducted in several settings. There are two types of incretin: Glucose dependent Insulinotropic Peptide (GIP) and Glucagon-like Peptide 1 (GLP-1). There is no question that incretin-based glucose-lowering medications have demonstrated to be effective glucose-lowering drugs. They proved an evidence-based efficacy profile and appear to do so with significant effects to stimulate weight loss with minimal hypoglycaemia. However, there are few side effects that should not be overlooked when deciding to use such therapies. Conclusion: The findings of our review presented here, do not prove that these agents are unsafe, but it does suggest that the burden of evidence now rests with those who hope to persuade us of their safety. Continuous clinical monitoring and more research are essential to clarify the actions of GLP-1R agonists and DPP-4 on the normal and diabetic exocrine pancreas.